Transação penal nos juizados especiais criminais: da legalidade ao empirismo - Dellaqua, Leonardo Goldner (2019)
Before the Court of Transactional Justice and Procedural Legal Transactions, the insertion of this model in Law and in the Criminal Procedure became evident reality implemented in several rules and sparse laws of the Brazilian Legal Order, bringing their significant expressions in the law of the Special Courts through the Institute of the Criminal Transaction. The possibility of negotiating the course of proceedings in the criminal sphere, allowing the defendant to choose the procedural path to follow, giving consequences that are different from those known in our classic model of criminal procedure, arose at a time when the system of criminal prosecution proves to be deficient , inefficient, due to the overcrowding of state structure and increasing crime. Although Law 9.099 / 95, with regard to the Special Criminal Courts, establishes guidelines for criminal transaction when dealing with the Transaction, its wording is still lacking in several points, requiring profound repairs and a general revision, in order to standardize its application in the various Special Criminal Courts of the Country. The simplicity of the procedure soon loses its characteristics given this gap writing, endowed with innumerable non technical skills, resulting in long discussions and various doctrinal positions that are often opposed. Although the law itself presents directives in its text, playing the role of true guiding principles, the procedure, in the face of legal omissions, ends up becoming more complicated than it should be. In this panorama, in the face of legislative confusion, questions arise regarding the ownership of the proposed transactions, the alleged obligation of the transaction and its possibility in private criminal lawsuits. The issues surrounding the consequences in case of noncompliance with the transaction agreed upon in a hearing are raised, once again the legal omission, and what appeals are appropriate to the sentence of a judge who ratifies the transaction. In turn, the legal nature of this decision of the Judge is still discussed, when it ratifies the Criminal Transaction, if convicted or homologated, in the pre-procedural phase or in the middle of a process. In the legislative obscurity, several Courts adopt innumerable different positions, if not contrary, disconnecting from these endless academic discussions when the Institute is in practice. In this context, it is necessary an empirical analysis intertwined with the directions given by the system of Criminal Transaction Justice and its legal provisions, in order to adapt or improve the procedure without violating rights or trampling steps.